Short-Lived Immunity After 17DD Yellow Fever Single Dose Indicates That Booster Vaccination May Be Required to Guarantee Protective Immunity in Children - Campi-Azevedo, Ana Carolina; Reis, Laise Rodrigues; Peruhype-Magalhães, Vanessa; Coelho-dos-Reis, Jordana Grazziela; Antonelli, Lis Ribeiro; Fonseca, Cristina Toscano; Costa-Pereira, Christiane; Souza-Fagundes, Elaine Maria; Costa-Rocha, Ismael Artur da; Mambrini, Juliana Vaz de Melo; Lemos, Jandira Aparecida Campos; Ribeiro, José Geraldo Leite; et al. (Frontiers in Immunology, 2019)
The Yellow Fever (YF) vaccination is recommended for people living in endemic areas and represents the most effective strategy to reduce the risk of infection. Previous studies have warned that booster regimens should be considered to guarantee the long-term persistence of 17DD-YF-specific memory components in adults living in areas with YF-virus circulation. Considering the lower seroconversion rates observed in children (9-12 month of age) as compared to adults, this study was designed in order to access the duration of immunity in single-dose vaccinated children in a 10-years cross-sectional time-span. The levels of neutralizing antibodies (PRNT) and the phenotypic/functional memory status of T and B-cells were measured at baseline, 30-45-days, 1-year, 2-years, 4-years, 7-years and 10-years following primary vaccination. The results revealed that a single dose induced 85% of seropositivity at 30-45 days and a progressive time-dependent decrease was observed as early as 2 years that decline towards critical values (below 60%) at time-span ≥4-years. Moreover, short-lived YF-specific cellular immunity, mediated by memory T and B-cells was also observed after 4-years. Predicted probability and resultant memory analysis emphasize that correlates of protection (PRNT; effector memory CD8+ T-cells; non-classical memory B-cells) wane to critical values within ≥4-years after primary vaccination. Together, these results clearly demonstrate the decline of 17DD-YF-specific memory response along time in children primarily vaccinated at 9-12 months of age and support the need of booster regimen to guarantee the long-term persistence of memory components for children living in areas with high risk of YF transmission.